(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
This study focus as the flow behaviour of boundary layer Casson fluid embedded in an inclined stretching sheet in existence of stagnation point viscous dissipation and mass transfer. Governing equations are modified to ordinary differential equation through similarity techniques. Results of several physical parameters over velocity, temperature field, concentration, coefficient of skin friction, Nusselt and Sherwood number are demonstrated through graphical representation and discussed.